Oxidative Phosphorylation System in Gastric Carcinomas and Gastritis. (28th June 2017) - Feichtinger, René G.; Neureiter, Daniel; Skaria, Tom; Wessler, Silja; Cover, Timothy L.; Mayr, Johannes A.; Zimmermann, Franz A.; Posselt, Gernot; Sperl, Wolfgang; Kofler, Barbara
Abstract : Switching of cellular energy production from oxidative phosphorylation (OXPHOS) by mitochondria to aerobic glycolysis occurs in many types of tumors. However, the significance of this switching for the development of gastric carcinoma and what connection it may have to Helicobacter pylori infection of the gut, a primary cause of gastric cancer, are poorly understood. Therefore, we investigated the expression of OXPHOS complexes in two types of human gastric carcinomas ("intestinal" and "diffuse"), bacterial gastritis with and without metaplasia, and chemically induced gastritis by using immunohistochemistry. Furthermore, we analyzed the effect of HP infection on several key mitochondrial proteins. Complex I expression was significantly reduced in intestinal type (but not diffuse) gastric carcinomas compared to adjacent control tissue, and the reduction was independent of HP infection. Significantly, higher complex I and complex II expression was present in large tumors. Furthermore, higher complex II and complex III protein levels were also obvious in grade 3 versus grade 2. No differences of OXPHOS complexes and markers of mitochondrial biogenesis were found between bacterially caused and chemically induced gastritis. Thus, intestinal gastric carcinomas, but not precancerous stages, are frequently characterized by loss of complex I, and this pathophysiology occurs independently of HP infection.